Biomedicalization of end-of-life conversations with medically frail older adults - Malleable and senescent bodies. (December 2021) - Carter, Celina; Mohammed, Shan; Upshur, Ross; Kontos, Pia
Abstract: The common practice of delaying and/or avoiding end-of-life conversations with medically frail older adults is an important clinical issue. Most research investigating this practice focuses on clinician training and developing conversation skills. Little is known about the socio-political factors shaping the phenomenon of end-of-life conversations between clinicians and medically frail older patients. Using the critical lens of biomedicalization we consider how two dominant discourses, successful aging and frailty, and subsequent constructions of bodies as malleable or senescent, shape patient subjectivities and influence normative expectations about appropriate healthcare conversations and the consumption of biomedicine for medically frail adults. We highlight the uneven ways medically frail older adults are clinically positioned as successful or frail agers and briefly discuss how gender, class, and race may impact this tension and ambiguity. We conclude by arguing that end-of-life conversations with medically frail older adults is constrained by the pervasiveness of the successful aging discourse and the tendency within medical institutions to construct older bodies as malleable and in need of medical intervention to promote health and longevity. Highlights: First critical examination of socio-political factors shaping EOL conversations with medically frail older adults Genealogy of discourses, successful aging and frailty, highlighting their influence on the self, body and EOL conversations Ontological assumptions about medically frail bodies as malleable or senescent informs appropriateness of EOL conversations Future research should examine discourses, social structures and EOL conversations.